Does maternity leave affect child health? Evidence form Parental Leave in Australia survey - Khanam, Rasheda; Nghiem, H.S.; Connelly, L.B. (My University, 2009)
One of the arguments that is advanced in support of paid maternity leave (PML) policies is that the mother's time away from work, around childbirth, is expected to improve maternal health and child health and development. However evidence on these links is scarce and, until recently, little was known about the link, if any, between child health and maternity leave. Moreover, the limited literature that does exist tends to use aggregate data (i.e., an ecological design ) to test the hypotheses that maternity leave affects maternal and child health. Evidence from micro-level data is rare because of the unavailability of such data on household level. We employ such data from the Parental Leave in Australia Survey (PLAS), which is a nested survey of the Longitudinal Study of Australian Children (LSAC), to examine the impacts of maternity leave on child health. Using the PLAS and the first two waves of the LSAC we find that maternity leave, as measured by the duration of paid maternity leave (PML) and other forms of leave around childbirth have strong and statistically significant effects on: child health, the decision to breastfeed, the duration of breastfeeding, and the probability that child immunisations are up-to-date. Our results show that mothers who take maternity leave are more likely to breastfeed their children and also that longer-term maternity leave is associated with an increase in the duration of breastfeeding. Our results also confirm that both mothers' PML and fathers' paid paternity leave (PPL) have statistically significant and positive effects on general health status of children. We also find that, in most specifications, the effects of PML are significant if the duration of leave is at least 6 weeks. PML is also significantly associated with a lower probability of some childhood chronic conditions such as asthma and bronchiolitis, but the effects of PPL on these conditions is ambiguous.
Keywords: Employment; Employment -- Parental leave; Labour market; Employment; Parental leave; Employment and unemployment